Plan de marketing para la empresa café frontera: construcción de obras civiles de la ciudad de Loja - Suarez, José Antonio (2016)
This research work aims to develop a marketing plan for the company Café Frontera; Constructions of Civil Works of the city of Loja, aimed at better positioning in the local market in the field of construction. It was held in the city of Loja, to the effect methods as were used: inductive, deductive, analytical, synthetic order to synthesize all the information, and techniques applied as direct observation allowing to observe and assimilate the actual information the facts, and the survey was applied to 20 customers and 10 employees of the company as well as the interview with the manager. the situational analysis of the company to analyze the external aspects of the internal environment aspects, in order to establish the current status of how the company is performed, also. Thus we have the EFE matrix with a value of 2.70 points which means that there is a predominance of opportunities over threats; while EFI matrix with a value of 2.76 points, which means that there is a predominance of strengths over weaknesses. It could determine strengths, weaknesses, opportunities and threats for the design matrix High Impact, the same which identified strategic objectives with their respective budgets and responsible; the construction company does not have a marketing plan, what influences their sales; by not having an advertising plan that will help increase its position in the local and national market; It lacks a logo that identifies the company. Employees who work do not pay much interest in their work so they feel unmotivated, even more do not have a constant training to help them provide quality service.